CROSS-CULTURAL SYMBOLISM OF BIRDS AND ANIMALS: A COMPARATIVE STUDY OF ENGLISH AND UZBEK PERSPECTIVES (Modern education and development, 2025)
This article explores the symbolic meanings of selected birds and animals in English and Uzbek cultures, focusing on how these symbols reflect unique cultural perspectives and values. By examining the eagle and nightingale as bird symbols, and the fox and wolf as animal symbols, the study highlights the ways each language uses nature to express ideas about freedom, intelligence, resilience, and beauty. Through this comparative analysis, we gain insights into the cultural values embedded in language, as well as the similarities and distinctions in English and Uzbek worldviews. Understanding these symbolic associations enriches intercultural understanding and sheds light on how different societies interpret the natural world.Ushbu maqola ingliz va o‘zbek madaniyatlarida tanlangan qush va hayvonlarning ramziy ma’nolarini o‘rganadi va bu ramzlarning o‘ziga xos madaniy qarashlar va qadriyatlarni qanday aks ettirishi haqida fikr yuritadi. Maqolada burgut va bulbul qush ramzlari sifatida, tulki va bo‘ri esa hayvon ramzlari sifatida ko‘rib chiqiladi. Ular orqali har bir tilning tabiat orqali erkinlik, zukkolik, bardoshlilik va go‘zallik kabi tushunchalarni qanday ifoda etishi tahlil qilinadi. Ushbu qiyosiy tahlil orqali madaniyatlararo tushunishni chuqurlashtirib, ingliz va o‘zbek tilidagi dunyoqarashlar o‘rtasidagi o‘xshashlik va farqlarni ochib beradigan qimmatli ma’lumotlar olish mumkin.В данной статье рассматриваются символические значения, приписываемые определённым птицам и животным в английской и узбекской культурах, а также то, как эти символы отражают уникальные культурные ценности и взгляды. В статье исследуются образы орла и соловья в качестве символов среди птиц, а также образы лисицы и волка среди животных, анализируя, как каждый язык через природу выражает такие понятия, как свобода, ум, стойкость и красота. Этот сравнительный анализ углубляет межкультурное понимание, раскрывая сходства и различия в мировоззрениях, выраженных через английский и узбекский языки.